Features of the Application of Ethnometric Methodology in the Context of the Study of Democratic Transitions - Galstyan, Khachik (YSU Journal of International Affairs, 2022)
The main purpose of this study is to identify the features of the application of ethnometric methodology in the context of the study of democratic transitions. This methodology, proposed by the Dutch researcher G. Hofstede, was initially used to identify patterns in the formation of business culture in different countries, as well as between political conflicts and violent phenomena.Within the framework of the article, in the context of the experience of the democratic transition of the “third wave” countries, four main ethnometric indicators of G. Hofstede are considered: distance from power (PDI), masculinity (MAS), uncertainty avoidance (UAI) and individualism (IDV). In particular, it is argued that in those countries where high indicators of power distance (PDI) are observed, the process of democratic consolidation is slowing down and does not contribute to theformation of dialogue practices. And in the case of a certain “dialogue attraction”, the main actors in the political field - the authorities and the opposition, show political will, seek to level the problems that have accumulated in society, including the uneven distribution of state resources, direct political processes towards theinstitutionalization of political dialogue.The article also examines the paradigm of democratic transition, some patterns and relationships between the culture of political dialogue and democratic transition, etc.
Keywords: ethnometrics; culture of political dialogue; democratic transition; Power Distance Index (PDI); Masculinity Index (MAS); Uncertainty Avoidance Index (UAI); Individualism Index (IDV)